2021
DOI: 10.1186/s12891-021-04457-5
|View full text |Cite
|
Sign up to set email alerts
|

Whether sutures reduce the graft laceration caused by interference screw in anterior cruciate ligament reconstruction? A biomechanical study in vitro

Abstract: Background Interference screw is commonly used for graft fixation in anterior cruciate ligament (ACL) reconstruction. However, previous studies had reported that the insertion of interference screws significantly caused graft laceration. The purposes of this study were to (1) quantitatively evaluate the graft laceration from one single insertion of PEEK interference screws; and (2) determine whether different types of sutures reduced the graft laceration after one single insertion of interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Compression fixation (i.e., interference screw) provides aperture fixation, but the screw often pushes the graft to the side during the screw insertion into the tunnel, reducing the tendon‐bone contact area, and the thread can damage the graft. A study showed that the ultimate failure load of graft was reduced by approximately 25% due to graft laceration by the interference screw 28 . Suspensory fixation allows for circumferential tendon‐bone contact, but its fixation point far away from the joint line can produce a “bungee effect” and a “windshield wiper effect” with cyclic loading 29–31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compression fixation (i.e., interference screw) provides aperture fixation, but the screw often pushes the graft to the side during the screw insertion into the tunnel, reducing the tendon‐bone contact area, and the thread can damage the graft. A study showed that the ultimate failure load of graft was reduced by approximately 25% due to graft laceration by the interference screw 28 . Suspensory fixation allows for circumferential tendon‐bone contact, but its fixation point far away from the joint line can produce a “bungee effect” and a “windshield wiper effect” with cyclic loading 29–31 .…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the ultimate failure load of graft was reduced by approximately 25% due to graft laceration by the interference screw. 28 Suspensory fixation allows for circumferential tendon-bone contact, but its fixation point far away from the joint line can produce a "bungee effect" and a "windshield wiper effect" with cyclic loading. [29][30][31] Transtunnel (i.e., RigidFix cross pins) could avoid eccentric fixation and graft injury caused by interference screws, also avoiding the "bungee effect" and "windshield wiper effect" caused by suspensory fixation, which is conducive to graftbone incorporation.…”
Section: Graft Fixation Stylementioning
confidence: 99%